2021
DOI: 10.1182/blood.2020005964
|View full text |Cite|
|
Sign up to set email alerts
|

TLR9 expression in chronic lymphocytic leukemia identifies a promigratory subpopulation and novel therapeutic target

Abstract: CLL remains incurable despite BCR-targeted inhibitors revolutionizing treatment. This suggests that other signaling molecules are involved in disease escape mechanisms and resistance. Toll-like receptor 9 (TLR9) is a promising candidate, which is activated by unmethylated CpG-DNA. Here, we show that plasma from CLL patients contains significantly more unmethylated DNA than plasma from healthy controls (p<0.0001) and that cell-free DNA levels correlate with the prognostic markers CD38, b2-microglobulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 62 publications
0
22
0
Order By: Relevance
“…Previously our group had reported that stimulating CLL cells with a TLR9 agonist, ODN2006, significantly increased CLL cell migration in 2D transwell systems [ 38 ]. We investigated if CLL migration was a FAK-dependent process by establishing whether TLR9 agonism induced p-FAK and by pharmacological inhibition of FAK using defactinib.…”
Section: Resultsmentioning
confidence: 99%
“…Previously our group had reported that stimulating CLL cells with a TLR9 agonist, ODN2006, significantly increased CLL cell migration in 2D transwell systems [ 38 ]. We investigated if CLL migration was a FAK-dependent process by establishing whether TLR9 agonism induced p-FAK and by pharmacological inhibition of FAK using defactinib.…”
Section: Resultsmentioning
confidence: 99%
“…The TLR9 receptors are localized on the membrane of endosomal compartments, where they interact with internalized CpG ODNs for signaling activation. 46 , 47 , 48 , 49 We therefore examined the subcellular localization of CpG FAM NP and CpG FAM NP@M R . LysoTracker is a fluorescent dye that labels acidic organelles such as the endolysosomes.…”
Section: Resultsmentioning
confidence: 99%
“… 42 The pathogenetic activation of BCR signaling and TLR signaling synergistically promote the proliferation and survival of CLL cells. 50 Targeting BTK, a critical component of BCR signaling, has emerged as a promising therapeutic approach against CLL. Although BTK is also involved in TLR pathway, the single use of BTK inhibitors only partly dampened the activation of TLR pathway in CLL cells, which accounted for the low complete remission rate for CLL patients who received BTK inhibition treatment.…”
Section: Btk In Immunological Signaling Pathwaysmentioning
confidence: 99%